Analysıs Of Effect Of Reproductıve Health Educatıon And The Normal Sex Educatıon Currıculum On Undergraduate Students' Sexualıty In South-South Nıgerıa - Christiana C. Ihejiamaizu; German E Anagbogu; Francisca N. Odigwe (European Scientific Journal, ESJ, 2016)
The study is a comparative analysis of effect of reproductive health education and normal curriculum teaching on undergraduate students' sexuality. Research question was raised and converted to a hypothesis which states that there is no significant difference between the effects of reproductive health education and normal sex education curriculum on undergraduate students sexuality. The study used a sample of four hundred (400) respondents randomly selected from the six federal universities in south-south zone of Nigeria. The design adopted was the quasi experimental design on a pre-test post-test control group with factorial arrangement. The result from the data analysis revealed that there was a significant difference between the effects of reproductive health education and normal sex education curriculum on undergraduate students' sexuality in all the treatment groups, but there was no significant difference given their access to the media and socio-economic background. Conclusion was drawn and it was recommended that a more comprehensive reproductive health education content be developed and explained as an informal educational programme for undergraduate students to curb the increase in the bottlenecks involved in the use of the sex education content taught in most Nigerian schools.